Učinkovitost ali uspešnost organizacije - Potočan, Vojko (Organizacija (Kranj), 2005)
Organisations assure their existence and development, which must be requisitely effective. Attainment of a requisite level of efficiency and effectiveness is a complex problem, which can be resolved if one requisitely holistically understands and revolves numerous real and fictitious conflicts. The latter show up while efficiency and effectiveness are dealt with from different viewpoints, organisation levels, areas of work, and behaviour. This contribution discusses two theses: 1) one should more holistically understand synergies of efficiency and effectiveness attainment; 2) relations between efficiency and effectiveness from the viewpoint of conflict resulting from attaining in the working and functioning of organizations.
Keywords: podjetja; učinkovitost; efficiency; poslovna uspešnost; uspešnost poslovanja